Impact of Hoarding and Obsessive–Compulsive Disorder Symptomatology on Quality of Life and Their Interaction With Depression Symptomatology - Nguyen, Binh K.; Zakrzewski, Jessica J.; Sordo Vieira, Luis; Mathews, Carol A. (Frontiers in Psychology, 2022)
Hoarding disorder (HD) is a psychiatric condition characterized by difficulty discarding items and accumulation of clutter. Although studies have established the negative impact of HD and compulsive hoarding behavior, fewer have examined the impact on quality of life (QoL) of hoarding behavior independent of obsessive-compulsive disorder (OCD). Moreover, specific aspects of QoL such as success in work/academics or satisfaction with interpersonal relationships have not been well-studied. In this study, we examined, in a sample of 2,100 adult participants obtained from Amazon Mechanical Turk, the relationships between hoarding, OCD, and depression symptomatology and four QoL domains (success, enrichment, environment, and family) derived from a factor analysis of the Quality of Life Inventory (QoLI). We performed linear regressions to examine associations between psychiatric symptomatology and QoL domains and then conducted mediation analyses to investigate the role of depressive symptomatology in the identified relationships. We found that while hoarding and obsessive-compulsive symptoms were both negatively associated with QoL, they were associated with different domains (hoarding was significantly associated (p <0.05) with overall QoL and all domains and uniquely associated with environment and family QoL compared to obsessive-compulsive symptoms), whereas obsessive-compulsive symptoms were only significantly associated with total, success, and enrichment QoL). However, when depressive symptoms were included in the model, hoarding no longer accounted for significant variance in the total, environment, or family QoL domains (p >0.05), and was less strongly associated with success or enrichment. Mediation analyses confirmed the role of depression as a complete mediator of hoarding’s effect on total, environment, and family QoL, and as a partial mediator of hoarding’s effect on success and enrichment QoL. Further examination of the relationship between hoarding symptoms and QoL within those with mild, moderate, and severe depression indicated that in those with more severe depression, hoarding was associated with improved QoL, indicating a possible buffering or compensatory effect. The findings suggest a differential impact of hoarding and obsessive-compulsive symptoms on QoL and the importance of considering co-morbid depressive symptoms in designing more targeted interventions. Future studies should continue to investigate these complex relationships, given the high co-morbidity of hoarding and depression.